In vitro and in vivo protective efficacies of antibodies that neutralize the RNA N-glycosidase activity of Shiga toxin 2. - Jeong, Kwang-il.; Chapman-Bonofiglio, Susan.; Singh, Pradeep.; Lee, Jongo.; Tzipori, Saul.; Sheoran, Abhineet S. (2016)
Backgound: Shiga toxin 2 (Stx2), one of two Stx liberated by Stx-producing Escherichia coli, is composed of an A subunit monomer and a B subunit pentamer, and is directly linked with hemolytic uremic syndrome in children. The pentameric B subunit binds to its cell surface receptor Gb3 for toxin internalization, and the A subunit follows intracellular retrograde transport to the cytosol where its RNA N-glycosidase activity (RNA-NGA) shuts down the protein synthesis, and leads to cell death. The present study investigated the ability of 19 Stx2 A subunit-specific human monoclonal antibodies (HuMAbs) to neutralize the RNA-NGA, and the association this neutralizing activity with protection of HeLa cells and mice against Stx2-induced death.; Keywords: Shiga toxin, Stx-producing Escherichia coli, hemolytic uremic syndrome, globotriaosyl ceramide, globotetraosylceramide, trans-Golgi network, endoplasmic reticulum, human monoclonal antibodies, RNA N-glycosidase activity, Stx-producing Escherichia coli, hemolytic uremic syndrome.; Springer Open.